NFATc1 supports imiquimod-induced skin inflammation by suppressing IL-10 synthesis in B cells - Hani Alrefai (Nature Portfolio, 2016)
Regulatory B cells are important for preventing skin autoimmunity. Here the authors show that NFATc1 suppresses IL-10 transcription in regulatory B cells, and inhibiting NFATc1 decreases immunopathology in a mouse model of imiquimod-induced skin inflammation.